2020
DOI: 10.5897/ajest2020.2871
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo diversity and carbon stocks of dominant species in different agro-ecological zones in Cameroon

Abstract: Bamboo is of ecological and socioeconomic importance in the world. However, knowledge on its potential in climate change mitigation remains superficial in Cameroon. The present study identified bamboo diversity and estimated carbon stocks of the dominant species in Cameroon. Ground truth method and local informants were used for a bamboo species survey in five Agro-ecological zones (AEZs). Twenty-two circular plots of 100 m² each were utilized for biomass and density data collection in AEZ 2, AEZ 3 and AEZ 4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
1
3
2
Order By: Relevance
“…The bamboo clumps in compartment 69 had notable truncated shoots showing evidence of destructive sampling of culms from past research. Comparatively, the culm density of 3710 culms ha À1 for this study is higher than culm densities of 2296 and 2933 culms ha À1 reported for B. vulgaris from Cameroon [17] and Bangladesh [18] respectively, but lower than 4800 culms ha À1 reported in North-East India [33]. The variations in culm densities could emanate from the different silvicultural management practices in other countries.…”
Section: B Vulgaris Distribution Densitycontrasting
confidence: 73%
See 3 more Smart Citations
“…The bamboo clumps in compartment 69 had notable truncated shoots showing evidence of destructive sampling of culms from past research. Comparatively, the culm density of 3710 culms ha À1 for this study is higher than culm densities of 2296 and 2933 culms ha À1 reported for B. vulgaris from Cameroon [17] and Bangladesh [18] respectively, but lower than 4800 culms ha À1 reported in North-East India [33]. The variations in culm densities could emanate from the different silvicultural management practices in other countries.…”
Section: B Vulgaris Distribution Densitycontrasting
confidence: 73%
“…It is important to note that accuracy of biomass estimation improves as the number of field samples increases [35]. The aboveground biomass recorded in this study greatly differs from aboveground biomass values of 53.42 Mg ha À1 [36] and 63.02 t ha À1 [17] recorded for B. vulgaris in a school research farm in India and a closed tropical broad-leaved rainforest in Cameroon, respectively. The wide variations may be attributed to the ecological zone, the method of inventory, and the allometric models used for biomass estimation.…”
Section: Aboveground Biomasscontrasting
confidence: 65%
See 2 more Smart Citations
“…Such efforts are vital for maintaining the health of watersheds and the ecosystems they support. The loss or alteration of key species can have farreaching consequences, impacting not only the ecosystem but also the communities and plant species like Telfairia occidentalis that rely on these water bodies for sustenance and recreation (Martin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%